OBYEK GRUP DAN OBYEK KOGRUP DARI SEBUAH KATEGORI - Puspita, Nikken Prima; Wijayanti, Indah Emilia; Susanti, Yeni (MATEMATIKA, 2010)
. A category contained a classes of objects and morphism betweenÂ  two object. For any chategory with initial object, terminal object, product and coproduct can defined a special object i.e group object and cogroup object. Object group obtained from cathegory object which have fulfil definition like definition a group. The cogroup object is dual from group object. Â